New insights into the interplay between autophagy and cartilage degeneration in osteoarthritis - Lv, Xiaoman; Zhao, Ting; Dai, Youwu; Shi, Mingqin; Huang, Xiaoyi; Wei, Yuanyuan; Shen, Jiayan; Zhang, Xiaoyu; Xie, Zhaohu; Wang, Qi; Li, Zhaofu; Qin, Dongdong (Frontiers in Cell and Developmental Biology, 2022)
Autophagy is an intracellular degradation system that maintains the stable state of cell energy metabolism. Some recent ﬁndings have indicated that autophagy dysfunction is an important driving factor for the occurrence and development of osteoarthritis (OA). The decrease of autophagy leads to the accumulation of damaged organelles and macromolecules in chondrocytes, which affects the survival of chondrocytes and ultimately leads to OA. An appropriate level of autophagic activation may be a new method to prevent articular cartilage degeneration in OA. This minireview discussed the mechanism of autophagy and OA, key autophagy targets regulating OA progression, and evaluated therapeutic applications of drugs targeting autophagy in preclinical and clinical research. Some critical issues worth paying attention to were also raised to guide future research efforts.